Philistinism: plain words concerning certain forms of modern scepticism - Newton, R. Heber (G.P. Putnam's Sons, 1886)
Concerning "philistinism" and its Goliath -- Christianity and its critics -- The Trinity and Original Sin -- Election and Atonement -- The Resurrection of the body and future punishment -- The mystery of matter -- Mind in nature -- Design in nature -- The problem of pain in the animal world -- The problem of human pain -- Jesus--the Christ -- Immortality in the light of physical science.